2019
DOI: 10.1016/j.chemosphere.2019.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the widespread occurrence of short- and medium-chain chlorinated paraffins in fish collected from the Rhône River basin (France)

Abstract: Chlorinated paraffins (CPs) are high-volume chemicals used in numerous industrial applications. Their quantitative analysis is extremely challenging and this work presents the optimization of an analytical method based on gas chromatography hyphenated with electron capture negative ionization timeof-flight high-resolution mass spectrometry (GC-ECNI-TOF HRMS) for the simultaneous determination of short-chain and medium-chain CPs (SCCPs and MCCPs, respectively) in fish tissues (i.e. dorsal muscle). The resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…A recent study by Kraẗschmer et al 19 determined concentration ranges for SCCP of 0.97−170 ng/g and MCCP of 1.1−79 ng/g of fresh weight in fish, with higher MCCP levels on average. A study by Labadie et al 20 wet weight) than SCCP concentrations (0.3−10.6 ng/g of wet weight) in fish. The trend of SCCP concentrations becoming lower and MCCP concentrations becoming higher occurs even more in this pilot study.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A recent study by Kraẗschmer et al 19 determined concentration ranges for SCCP of 0.97−170 ng/g and MCCP of 1.1−79 ng/g of fresh weight in fish, with higher MCCP levels on average. A study by Labadie et al 20 wet weight) than SCCP concentrations (0.3−10.6 ng/g of wet weight) in fish. The trend of SCCP concentrations becoming lower and MCCP concentrations becoming higher occurs even more in this pilot study.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In the aquatic environment, SCCPs are more likely to be adsorbed in sediment since they have low water solubility and high carbon partition coefficients (Environment Canada 2008). There are quite a number of studies that have been reported globally (Wang et al 2019a;Pan et al 2018;Pan et al 2020;Huang et al 2019a;Wang et al 2020a;Labadie et al 2019).…”
Section: Aquatic Environmentmentioning
confidence: 99%
“…The concentrations of SCCPs in farmed freshwater fish and wild sea fish ranged from 220 to 51000 ng g −1 lw and 900 to 7300 ng g −1 with ∑SCCP concentration of 5900 ± 8100 ng/g lw and 3000 ± 1600 ng/g lw, respectively. Labadie et al (2019) determined SCCP concentration in fish samples from the Rhone River basin, France. SCCP concentration ranged from 0.3 to 10.6 ng g −1 wet weight (ww) which were in the same order of magnitude with those reported by Saborido Basconcillo et al (2015), Herzke et al (2013) and Parera et al (2013).…”
Section: Sedimentmentioning
confidence: 99%
“…For most of the fish samples, SCCPs showed higher concentrations than MCCPs, while in the fish oil and cod liver oil samples the contribution varied depending on the sample. In the study mentioned above for SCCPs, Labadie et al (2019) also analysed MCCPs in the common barbel. MCCPs were widespread with concentrations ranging from 1.3 to 72.7 lg/kg ww, which are higher than the values found for SCCPs.…”
Section: Mccpsmentioning
confidence: 99%